Peoples Perspective of CSR in Pakistan - Haider, Mubarak Hussain; Irfan, Malik Muhammad; Hashmi, Aijaz Mustafa (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Corporate social responsibility is now the legitimate concern for the future survival of the organizations. The companies that are aligned with corporate social responsibility in stake holders perspective will be competitively ahead of their competitors. All past researches focus have been on the companies perspective, what they do and how they do? First time this research was from the perspective of the people of Pakistan, what they think and expect from the companies. The data was collected from all provinces of Pakistan, Punjab, Khyber Pakhtun Khawa(KPK), Sind, Baluchistan, federal city (Islamabad), Azad Jamu Kashmir (AJK), including 24 cities of provinces. Total 5000 questionnaire were sent through mail and email to the people of all communities and departments such as Universities, colleges, schools, hospitals, parks, villages, factories, departmental stores, food streets etc. Telephone calls and self administered approach were also used to collect data and total 3275 (66%) questionnaires were received and 167 were rejected due to non conformity to research. The data was analyzed from qualified 3108 (62%) questionnaires. The data of questionnaire on 16 codes of CSR depicts that the people of Pakistan rated education number one, employment number 2, healthcare number 3 and environment protection on number four the main issues. The companies that follow the hierarchy selected by the people of Pakistan, education, employment, healthcare and environment protection will be more successful than the companies which do not follow the hierarchy. The new business entrepreneurs can take the advantage right from the start of the business by investing in education, creating more employment opportunities, investing in health care related issues and protecting the environment from pollution. The research has set a prerequisite for the new entrepreneur while considering CSR priorities in Pakistan.